Kebijakan Pengembangan Pariwisata Melalui Ajang Mojang Jajaka Sebagai Duta Pariwisata - Nadia Amalia; Ruslyandi (Jurnal Governansi, 2023)
Bogor Regency is one of the tourist destinations in Indonesia because it has a lot of tourism potential, such as nature tourism, cultural tourism, and others. The Department of Tourism and Culture involves these Mojang Jajaka accompanying in every government activity and assisting in promoting tourism or environmental issues, where tourism and culture are one of the PAD in Bogor Regency. This research is expected to be able to formulate a tourism development model through the Mojang Jajaka event or a policy implementation model in the context of developing special knowledge related to public policy. The theory used in this research is Edward III Communication, Resources, Disposition, Implementation and Bureaucratic Structure. The communication referred to in this research is the Bogor Regency Tourism and Culture policy to socialize the objectives of implementing the Bogor Regency Tourism Office's policy. Management tools according to Harrington Emerson in Phiffner John (1960) have five elements (5M), namely: Men, Money, Materials, and methods. The tendency or attitude in implementing the policy plays an important role in the success of the policy, therefore the implementer of the tourism policy stated in Law Number 10 of 2009 is based on the attitude and views held. The processes that exist in the bureaucracy can run if they are consistent, efficient and efficient so that they do not conflict with the existing bureaucratic regulations into 2 SOPs and the Distribution of Responsibilities in the Context of Policy Implementation for the development of tourism in the Mojang Jajaka event.